Theoretical analysis of the cost of processing machine parts - Жовтобрюх, Валерій Олексійович (Eastern-European Journal of Enterprise Technologies, 2012)
Choice of the optimal parameters of mechanical treatment of machine parts by the lowest cost of treatment is done. Concrete and practical recommendations for improving the technical and economic parameters of treatment are given